Kill Chain : Drone and the Rise of High-Tech Assassins - Cockburn, Andrew (London Verso, 2016)
Surveillance, technology, war, and the failed US policy of remote killing
Include Illustrations, Notes and Index
Keywords: Drone aircraft -- Targeted killing